2022
DOI: 10.1021/acsbiomaterials.2c01127
|View full text |Cite
|
Sign up to set email alerts
|

Cell Infiltrative Inner Connected Porous Hydrogel Improves Neural Stem Cell Migration and Differentiation for Functional Repair of Spinal Cord Injury

Abstract: The disadvantages of cell-adaptive microenvironments and cellular diffusion out of the lesion have limited hydrogel-based scaffold transplantation treatment for neural connectivity, leading to permanent neurological disability from spinal cord injury. Herein, porous GelMA scaffold was prepared, in which the inner porous structure was optimized. The average pore size was 168 ± 71 μm with a porosity of 77.1%. The modulus of porous hydrogel was 593 ± 4 Pa compared to 1535 ± 85 Pa of bulk GelMA. The inner connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Shi et al reported a porous GelMA scaffold in which the inner porous structure was optimized. The inner connected porous structure increased neural stem cell adhesion to the matrix and enhanced neuron differentiation [ 41 ]. The SEM pictures confirm that the 2.5/2.5G/GMA and 4GMA bioinks presented higher porosity than the more rigid bioinks (5/5G/GMA and 8GMA), which enhances their biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al reported a porous GelMA scaffold in which the inner porous structure was optimized. The inner connected porous structure increased neural stem cell adhesion to the matrix and enhanced neuron differentiation [ 41 ]. The SEM pictures confirm that the 2.5/2.5G/GMA and 4GMA bioinks presented higher porosity than the more rigid bioinks (5/5G/GMA and 8GMA), which enhances their biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…It may be because the macroporous structure enhances the exchange of nutrients and oxygen between the hydrogel and the external environment, enhancing the encapsulated cells' viability in the hydrogel during culture. 45 It was proved that the migration rate of cells could be adjusted by changing the ratio of bio-inks. At the same time, the ADSCs encapsulated in different proportions of GelMA/ dextran bio-inks could respond to the changes in the physical and chemical microenvironment of hydrogel and achieve a variety of physiological functions, which lays a foundation for the application of the microtissue array we prepared.…”
Section: Biocompatibility Of Gelma/dextran Hydrogelmentioning
confidence: 99%
“…To improve the structure and function of mesenchymal scaffolds in various tissue applications, to repair the vascular system after injury, to improve the recovery of parenchymal tissue after injury and to produce and deliver soluble proteins, the implantation of porous scaffolds into various cell models has gradually been used in tissue regeneration medicine in recent years [ 94 , 95 ]. In addition, implantation of cells into a three-dimensional scaffold has been used to improve cell survival, including processes such as angiogenesis, cell migration, invasion, differentiation, and tumor formation, by creating a microenvironment similar to that of the human body [ 96 , 97 ]. Synthetic, natural, and bioderived hydrogels can be utilized for 3D encapsulated tumor cell culture, reconstructing the ECM microenvironment in vitro.…”
Section: Three-dimensional (3d) Model Of Cell Culture In Vitromentioning
confidence: 99%